Pembelajaran Pecahan Senilai dengan Bermain Lego - Feli Ramury; Yusuf Hartono; Ratu Ilma Indra Putri (Didaktik Matematika, 2015)
This research aimed to produce learning trajectory in learning algorithm to find equivalent fractions using Lego in fourth grade. This study was associated with thematic integrative learning curriculum 2013 based PMRI. The method used was design research of type validation study that aimed to prove the theories of learning. Design research that consists of three stages; preliminary design, teaching experiments, and retrospective analysis were chosen to achieve the research objectives by designed Hypothetical Learning Trajectory (HLT). The research was conducted on 21 students of class IV SDN 16 Lembak. This study aimed to investigate how Lego can help students to learning equivalent fraction. Students learning activities that were conducted including: 1) determine the fractions using lego, 2) determine the equivalent fraction of fractions formed from Lego, and 3) connect the concept of equivalent fraction to the standard algorithm to find equivalent fractions. The results of this study indicate that a series of activities can help students in learning equivalent fraction.